TOURIST'S WILLINGNESS TO PAY FOR ENVIRONMENT REHABILITATION - Riza Firmansyah; Maria Oselaga (Journal of Tourism Destination and Attraction, 2021)
Kepulauan Seribu Marine National Park (TNKpS) which is the only national park in the world located in a capital city, is included as a part of the Kepulauan Seribu Administrative Regency, DKI Jakarta Province. Based on the decree of the Director of Forest Protection and Nature Conservation Number SK.05/VI-KK/2004 concerning the Zonation of the Kepulauan Seribu Marine National Park, not all TNKpS areas can be used as tourism destinations, because there are zones aimed at conservation of natural resources. According to the decree, TNKpS area is divided into 4 zones, namely the Core Zone, Protection Zone, Tourism Utilization Zone and Settlement Zone. One of the residential islands in TNKpS which is also the main destination for tourists for transit, is Harapan Island. Apart from being the main destination for tourists for transit, Harapan Island is the largest island in Seribu Utara sub-district. The cost of traveling to Kepulauan Seribu, especially to Harapan Island, is very affordable, between IDR 350,000 to IDR 400,000. This affordable cost makes Harapan Island a priority natural tourist destination for residents of Jabodetabek (Jakarta, Bogor, Tangerang, and Bekasi). Many tourism activities on Harapan Island have not only a positive impact on the local economy but also a negative impact on the environment. There are a lot of rubbish such plastic snack waste and damaged coral reefs in the snorkeling spots. The concept of Willingness to Pay (WTP) of tourists is the willingness of tourists to pay for the assessment of natural resources in order to improve environmental quality in the Harapan Island area. This study aims to estimate the WTP of tourists to travel on Harapan Island. The design of this study used quantitative methods by collecting data through interviews and distributing questionnaires online. The data were processed by descriptive method and the Contingent Valuation Method (CVM). The results show that the WTP of tourists is as much as IDR 32,976/person/visit that can be included in the price of a tour package. As much as IDR 518,161,947 per year is expected to help the costs of nature conservation on Harapan Island. Keywords: Kepulauan Seribu Marine National Park (TNKpS), Harapan Island, Contingent Valuation Method (CVM), Willingness to Pay (WTP).